Promoting Students’ Reading Comprehension Using Graphic Organizer: A Classroom Action Research - Neny Kartika Sari; Nur Arifah Drajati; Dewi Rochsantiningsih (International Journal of Language Teaching and Education, 2019)
This research aimed to describe the process of improving students’ reading comprehension of narrative text through graphic organizer strategy in SMP Regina Pacis Surakarta. It was conducted to the ninth year students, especially class VIII A as the subject of research. The researcher conducted a classroom action research. Achievement test, observation checklist and field note used as the tools of data collecting. The research findings showed that graphic organizer strategy was appropriate for teaching reading comprehension. Students’ mean score increased from 63 to 78. The students were able to map out basic components of the story such as setting, problem, goals, action, and outcomes. Graphic organizerprovides structure and organization so students were able to comprehend the story more effective.